Wybrane rękopiśmienne plany Kamieńca Podolskiego - Opyrchał, Leszek; Opyrchał, Urszula; Nahnybida, Rusłan (Studia Geohistorica, 2020)
The article discusses seven manuscripts with plans of Kamianets-Podilskyi, the most important frontier fortress of the Polish-Lithuanian Commonwealth. The plans in question were made in the second half of the 17th century and in the first half of the 18th century. The anonymous plan of the city and the castle is particularly valuable because it presents the view of the fortress before it was captured by the Ottoman army in 1672. Great importance to the study of changes in the fortress fortifications is held by the plans made by de Jean/Jacques Bonnelevay and Jan de Witte as they were produced by the hands of engineers who were responsible for the reconstruction of the fortifications.